The Effect Of Profitabilitas, Leverage And Growth On The Policies Deviden Of Manufacturing Industri Companies Listed On The Indonesia Stock Exchange - Renny Mointi; Rina Rina (Economy Deposit Journal (E-DJ), 2019)
This study aims to analyze the effect of profitability represented by the ratio of return on investment, leverage represented by the ratio of Debt to Equity Ratio and Growth to Dividend Policy (Dividend Payout Ratio) on Manufacturing companies listed on the Indonesia Stock Exchange. The sample used in this study amounted to 5 companies and used data from 2013 to 2018. Data analysis used multiple regression and classic assumption tests which included normality tests of multicollinearity tests and autocorrelation tests The results of the partial analysis with the t test and F test concluded that the variable Profitability (ROI) did not have a significant effect on the Dividend Leverage Policy (DER). It did not have a significant effect on the variable dividend policy. Return on investment the low dividend policy of the remaining 84.1! Determined by other variables not covered in this study. The implication of the results of this study is that Return on investment debt to equity ratio and Growth variable returns cannot be used as an indicator in determining a company's dividend policy